AI and Digital Health Synergy: Transforming India’s Economy for the Future - Shankarrao Deshmukh, Brijesh; Patil, Sandeep H.; Purandare, Pradnya; Kumar Gudla, Surya Pavan; Hundekari, Sheela; Vasavi, M.; Shrivastava, Anurag (Journal of Neonatal Surgery, 2025)
The convergence of Artificial Intelligence (AI) and digital health is poised to revolutionize India's economic landscape, driving innovation, efficiency, and inclusivity in healthcare delivery. This paper explores the synergistic potential of AI and digital health technologies in addressing India's unique healthcare challenges, such as accessibility, affordability, and scalability. By leveraging AI-driven diagnostics, telemedicine, predictive analytics, and personalized medicine, India can not only improve health outcomes but also foster economic growth through job creation, enhanced productivity, and the development of a robust digital health ecosystem. The study highlights key policy recommendations, technological advancements, and collaborative frameworks necessary to harness this synergy for sustainable economic transformation. As India positions itself as a global leader in digital health, this paper underscores the critical role of AI in shaping a healthier, more prosperous future.